Wordwalls as an Interactive Learning Tool for Teaching English Vocabulary - Rona Merita; Atour Rohman Syahroni (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2025)
Vocabulary mastery constitutes a critical foundation for effective language acquisition. The use of Wordwalls in interactive learning activities has been shown to have a positive effect on increasing student engagement and understanding, especially in learning English vocabulary. The purpose of this study was to identify the benefits of Wordwalls as an interactive digital learning for making the English learning experience more enjoyable and engaging. A descriptive qualitative research method was applied to gather information through classroom observations and student interviews. The present study highlights the instructional potential of Wordwall as a digital learning platform that significantly contributes to increasing students’ learning motivation, encouraging active participation, and enhancing their mastery of subject matter. Students enrolled in Semester 2B of the Early Childhood Islamic Education program at Pangeran Diponegoro University, Nganjuk, reported that the platform’s interactive features—such as quizzes, word-based games, and participatory tasks—offered an engaging learning environment that facilitated a more profound understanding of English language skills. These included not only vocabulary development but also sentence construction and oral communication competence. The findings suggest that Wordwall serves as an effective pedagogical tool in supporting interactive and student-centered English language instruction, with strong potential for integration into higher education curriculum, particularly within the framework of early childhood teacher education.